Analisis Kebangkrutan Perusahaan yang Terancam Delisting di Bursa Efek Indonesia - Putri Risnanti; Eny Kustiyah; Rochmi Widayanti (Universitas Proklamasi 45 Yogyakarta, 2019)
Corporate bankruptcy can be seen from the performance of the company's financial statements. The purpose of this study is to find out how the performance of companies with suspension status in 2018 from January to October in the Indonesia Stock Exchange with 2016-2017 financial statement research. There are 13 companies that have suspension status in 2018 and still publish their financial statements between 2016-2017. The detection tool used in this study is the modified Altman Z-score Multiple Discriminant Analysis. With the results of this study there are six companies in healthy positions in two years between 2016-2017, five companies in bankruptcy positions, one company with the first year in a healthy position while the second year going bankrupt, and one company experiencing bankruptcy in the first year and grey area in the second year.